Athletes for France or Athletes for the Church: Conflict between Sports Officials and Catholic Sportsmen during the Vichy Regime (1940–1944). (7th December 2018) - Rathbone, Keith
Abstract: This article explores the relationship between the Church and state during the Occupation through a close examination of the Vichy's programme of physical education and sports at the national, regional and local level. Vichy officials wanted physical culture to rejuvenate the French people after the defeat; Church officials saw athleticism as a way of attracting young men and women to the Church. Vichy's attempt to rationalize physical education and sports meant that it increasingly came into conflict with distinctly Catholic social sports spaces. At times that clash emerged from the anti-clericalism of local officials, many of them holdovers from the Popular Front. More commonly, however, devout Catholic officials struggled to negotiate between Catholic institutions' agendas and their own desire to bring physical culture to as many French people as possible. In unpacking the conflict between Catholic and secular sportsmen, this article stresses the continued agency of local sports stakeholders in challenging the ideology of the Vichy state.